ANALISIS STRATEGI PENGEMBANGAN EKOWISATA BAHARI PULAU LAUT KABUPATEN KOTABARU KALIMANTAN SELATAN Study Pada Pulau Samber Gelap, Tanjung Kunyit, Teluk Tamiang dan Pantai Gedambaan - Hidayatulah As-Syahri; Marijati Sangen; Ahmad Rifani (Universitas Lambung Mangkurat, 2018)
This study aims to determine (i) Internal environmental factors and weaknesses, (ii) determine factors of external environmental into opportunities and threats in the depvelopment of marine ecotourism in Kotabaru district, and (iii) appropriate strategic alternatives in the development of marine ecotourism in Kotabaru district This study use destriptive method with qualitative approach. Purposive sampling technique in use to select the sample of 60 tourism and 40 local people who were in Kotabaru district. Data analysis used IFAS, EFAS, SFAS and SWOT analysis. The result showed that factors of internal environment which became the strength in the development of ecotourism of Kotabaru district are very interesting tourism attraction. It can be seen from natural conditions which are still beautiful, and natural. It is free from pollution and noise, and has very beautiful coral reefs and sea plants, and it is spported by the attitude of local people whoare very friendly and open to tourism. While the factors internal environment which became the weakness in ecotourism of Kotabaru district are limited facilities and infrastructure in the form of limited power supplies, shortage of clean water. In addion, the condition of bad-condition roads caused travel time to reach the tourism attarcations very long. The other weaksness was tourism promotion which was still less than optimal. The factors of external environment which became the opportunities in the development of ecotourism in Kabupeten Kotabaru were the policies in the depelopment of tourism which are able to attract investors, tourism ttavel agents to open tour and travel services, the policies in development can drive business activites and icrease the sociey’s income and also the policies in the development of tourism can open opportunities to people in every tourism activities. The environmental factors which became threats in marine tourism development in kabupaten Kotabaru were : (1) the fisherman still used tools or equipment which can damage the sea ecosystem, (2) peple still dit not take good care of cleanliness of their living environment, (3) the low awareness of the people of importance of education (4) the development of tourism can influence the local culture wisdom, and (5) the policy of the regional development potencially disturb the activities of people in making their livings as their main jobs. Priority strategic alternative based on SWOT analysis are : (1) an integrated management of the marine ecotourism development of Kotabaru district-society-based, (2) monitoring the utilization of natural resources should not exceed the capacity of the environment by involving NGOs and government agencies, (3) cooperating with investors in improving tourism facilities nd tourism supporting infrastructure, (4) making tourism-aware group involving government, community, and business as mediators of tourism (5) increasing cooperation with local government with the stockholder in facing high competition, (6) making regular agenda of local cultute festival such as : Mappanretasi and traditional bat races as means of lokal toursm promotion, and (7) diving zones of the use of natural resources with tourism areas.